Swimming speed alteration of Artemia sp. and Brachionus plicatilis as a sub-lethal behavioural end-point for ecotoxicological surveys - Garaventa, Francesca (Ecotoxicology (London, England), 2010)
In this study, we investigated the possibility to improve a new behavioural bioassay (Swimming Speed Alteration test-SSA test) using larvae of marine cyst-forming organisms: e.g. the brine shrimp Artemia sp. and the rotifer Brachionus plicatilis. Swimming speed was investigated as a behavioural end-point for application in ecotoxicology studies. A first experiment to analyse the linear swimming speed of the two organisms was performed to verify the applicability of the video-camera tracking system, here referred to as Swimming Behavioural Recorder (SBR). A second experiment was performed, exposing organisms to different toxic compounds (zinc pyrithione, Macrotrol MT-200, and Eserine). Swimming speed alteration was analyzed together with mortality. The results of the first experiment indicate that SBR is a suitable tool to detect linear swimming speed of the two organisms, since the values have been obtained in accordance with other studies using the same organisms (3.05 mm s(-1) for Artemia sp. and 0.62 mm s(-1) for B. plicatilis). Toxicity test results clearly indicate that swimming speed of Artemia sp. and B. plicatilis is a valid behavioural end-point to detect stress at sub-lethal toxic substance concentrations. Indeed, alterations in swimming speed have been detected at toxic compound concentrations as low as less then 0.1-5% of their LC(50) values. In conclusion, the SSA test with B. plicatilis and Artemia sp. can be a good behavioural integrated output for application in marine ecotoxicology and environmental monitoring programs